Short-Term Beat-to-Beat QT Variability Appears Influenced More Strongly by Recording Quality Than by Beat-to-Beat RR Variability - Toman, Ondřej; Hnatkova, Katerina; Šišáková, Martina; Smetana, Peter; Huster, Katharina M.; Barthel, Petra; Novotný, Tomáš; Andršová, Irena; Schmidt, Georg; Malik, Marek (Frontiers in Physiology, 2022)
Increases in beat-to-beat variability of electrocardiographic QT interval duration have repeatedly been associated with increased risk of cardiovascular events and complications. The measurements of QT variability are frequently normalised for the underlying RR interval variability. Such normalisation supports the concept of the so-called immediate RR effect which relates each QT interval to the preceding RR interval. The validity of this concept was investigated in the present study together with the analysis of the influence of electrocardiographic morphological stability on QT variability measurements. The analyses involved QT and RR measurements in 6,114,562 individual beats of 642,708 separate 10-second ECG samples recorded in 523 healthy volunteers (259 females). Only beats with high morphology correlation (r>0.99) with representative waveforms of the 10-second ECG samples were analysed assuring that only good quality recordings were included. In addition to these high correlations, standard deviations of the ECG signal difference between representative waveforms and individual beats expressed morphological instability and ECG noise. In the intra-subject analyses of both individual beats and of 10-second averages, QT interval variability was substantially more strongly related to the ECG noise than to the underlying RR variability. In approximately one third of analysed ECG beats, the prolongation or shortening of the preceding RR interval was followed by the opposite change of the QT interval. In linear regression analyses, underlying RR variability within each 10-second ECG sample explained only 5.7% and 11.1% of QT interval variability in females and males, respectively. On the contrary, the underlying ECG noise contents of the 10-second samples explained 56.5% and 60.1% of the QT interval variability in females and males, respectively. The study concludes that the concept of stable and uniform immediate RR interval effect on the duration of subsequent QT interval duration is highly questionable. Even if only stable beat-to-beat measurements of QT interval are used, the QT interval variability is still substantially influenced by morphological variability and noise pollution of the source ECG recordings. Even when good quality recordings are used, noise contents of the electrocardiograms should to be objectively examined in future studies of QT interval variability.